Cancer neuroscience: state of the field, emerging directions - Winkler, Frank; Venkatesh, Humsa S.; Amit, Moran; Batchelor, Tracy; Demir, Ihsan Ekin; Deneen, Benjamin; Gutmann, David H.; Hervey-Jumper, Shawn; Kuner, Thomas; Mabbott, Donald; Platten, Michael; Rolls, Asya; et al. (Cell, 2023)
The nervous system governs both ontogeny and oncology. Regulating organogenesis during development, maintaining homeostasis, and promoting plasticity throughout life, the nervous system plays parallel roles in the regulation of cancers. Foundational discoveries have elucidated direct paracrine and electrochemical communication between neurons and cancer cells, as well as indirect interactions through neural effects on the immune system and stromal cells in the tumor microenvironment in a wide range of malignancies. Nervous system-cancer interactions can regulate oncogenesis, growth, invasion and metastatic spread, treatment resistance, stimulation of tumor-promoting inflammation, and impairment of anti-cancer immunity. Progress in cancer neuroscience may create an important new pillar of cancer therapy.
Gesehen am 15.06.2023